(untitled) (Journal of the Society for Musicology in Ireland, 2016)
The Dublin career of Tommaso Giordani as a theatre musician and composer is well known, but almost nothing has been known of his role in directing music at the Roman-Catholic chapel in Francis Street, Dublin, in the time of Archbishop John Thomas Troy. This article brings to light the fact that, when his musical library was auctioned at the beginning of the nineteenth century, it included a manuscript of the Messa per dodici cori con organo composed in 1774 by Gregorio Ballabene. The performance of such a work would be remarkable in Ireland at this date, and the existence of a copy is remarkable enough. In 1827 it was auctioned among the possessions of the parish priest of Francis Street Chapel, but where it went is not known.